The relationship between childhood maltreatment and mental health problems: coping strategies and social support act as mediators - Su, Yingying; Meng, Xiangfei; Yang, Guang; D’Arcy, Carl (BMC psychiatry, 2022)
Background Childhood maltreatment significantly increases the risk of developing mental health problems in adolescence and adulthood. The present study examines if coping strategies and social support mediate the relationship between childhood maltreatment and mental health problems. Methods Data analyzed were from the 2012 Canadian Community Health Survey Mental Health (CCHS-MH, N = 25,113), a national population survey. A structured diagnostic interview, the World Health Organization version of Composite International Diagnostic Interview (WHO-CIDI), was used to assess mental health status. Multiple mediation analysis with structural equation modelling is used to test the mediating effects of coping skills and social support in the relationship between childhood maltreatment and mental health problems. Results Our findings demonstrate that both coping strategies and social support mediated the link between childhood maltreatment and major depressive episode (mediation proportion: 18.3%), generalized anxiety disorder (mediation proportion: 19.8%), and suicide ideation (mediation proportion: 15.9%). By and large, the study results showed that coping skills and social support had both direct and indirect effects on the studied mental health problems with coping skills having a stronger impact. Conclusions Personal resources play an important resilience role in the associations between maltreatment and mental disorders with positive coping strategies, an internal resource, having a stronger protective presence. This research reinforces the need for strengthening positive coping strategies as well as social support as preventive strategies to improve mental health for individuals who have experienced childhood maltreatment.